Language as a tool for marginalization of disadvantaged students in Lebanon. (c2019) - Chatila, Samira N. (2019)
With the influx of Syrian refugees to Lebanon, the attention of research has focused on the marginalization and vulnerability of these children including their access to school. A lot of the discussion in this field has focused on the inability of Syrian refugee children to enroll in mainstream public Lebanese schools due to the language challenge, in particular learning mathematics and sciences in English and French. This has resulted in segregating Syrian children in afternoon school shifts. However, this discourse overlooks the effect of the colonial practices on the Lebanese educational system and how it has marginalized a large sector of the vulnerable Lebanese children attending public schools since Lebanon’s independence in 1943. The study investigates the interplay between the colonial history of Lebanon, today’s educational policies and practices, and school outcomes of children from disadvantaged socioeconomic backgrounds. It shifts the debate from the discourse of refugees being the problem to the inherited structural inequalities of the Lebanese educational system. The study follows a mixed method design with qualitative and quantitative components. It comprises a survey with students in addition to interviews with Lebanese and Syrian children, school principals, teachers, and parents. Classroom observations were also conducted. Mentors and trainers from the Lebanese Ministry of Education and Higher Education were also interviewed. Research findings revealed that foreign language was experienced as a barrier to learning and a source of marginalization by both Syrian and Lebanese students. The thesis raises questions concerning the language policy in Lebanon. It also questions the call to segregate and “dumb” down the curriculum for Syrian refugees in afternoon shift. Finally, it highlights the quality of teaching foreign languages in public schools and its effect on the attainment of children from disadvantaged socio-economic background.